MENGGAIRAHKAN KEHIDUPAN KAMPUS MENGGAPAI PELUANG BISNIS DALAM ARENA KREATIFITAS SENI BUDAYA - H. achmad Rifa'i (Jurnal Manajemen dan Bisnis, 2020)
Opportunities to intregrate business and service can e realized in managing the diversity of traditional cultural arts and creative entrepreneurship, which is very open in the area of banten Province, which is actively developing itself in various development sectors in order to improve the economy of Trans-Sumatra and Java islands and the National and International regions, supported by the existense of Tanjung Lesung Sepecial Economic Zone in Pandeglang Regency and the Sukarno-Hataa International Airport in tangerang City which is adjacent to Jakarta the Capital of the Unitary State of Republik Indonesia. The opportunity for a combination of business and preservation of cultural arts can be done by all parties from the Creative Economy Business Acto businessrs, Government and Society, as well as the Word of Education in Higher Education in the Region and National. These business opportunities need to be prepared through learning and research methods, as well as field practices initiated in synergy through the word of education in Higher Education, in that case they are also part of the Tri Dharma Higher Education’s practice of community service. Armed with critical, progressive and innovative thinking, studens shoul also be equipped with a real business movement in Existing Campus Life as Bridge to Create Business Opportunities in Banten Art and Culture Arena, which is also directly to realize the preservation of Regional Cultural Arts assets generally become the assets of National Culture Arts